(untitled) (Heritage, 2022)
This text will interpret the key concepts of postcolonialism and postcolonial studies with a reflection on the orientalist paintings of Paja Jovanović. The basics of the research concern the influence of the occident and colonizing countries on the artistic creation of Jovanović, with a critical analysis and comparison of the mentioned terms aiming to determine the characteristics of this painter’s orientalist expression through a case study of several of his works: The Wounded Montenegrin (1882), Fencing (1883), and Adorning of the Bride (1886). The theoretical basis for this research are mainly the postcolonial studies of Edward Said, Marija Todorova, and Bojana Matejić, aiming to determine the degree of implementation of orientalist discourse in the cultural heritage of the Serbian people.